Marketing de relacionamento no setor bancário : uma busca da fidelização de clientes após a portabilidade - Rezende, Gracielle Antunes Cangussú (2016)
The purpose of this paper is identify the relationship between the main dimensions of relationship marketing and customer loyalty in financial institutions after the implantation of the bank account portability system. Furthermore, this work was based in